Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Matematika Siswa pada Materi Relasi dan Fungsi SMP Negeri 2 Waingapu - Fincilia Haramburu; Darius Imanuel Wadu; Iona Lis Ndakularak (Mathematics Education Study Program, 2025)
This research aims to determine the effect of using the Problem Based Learning model on the relationship and function material for class VIII students at SMP Negeri 2 Waingapu for the 2024/2025 academic year. This research uses a quantitative approach with a quasi-experimental research design. The population of this research includes class VIII students in the 2022/2023 school year, consisting of 20 students in class VIII-A and 20 students in class VIII-B, the sample in the study consisted of 40 students. In this research, the data analysis techniques used include descriptive analysis and inferential analysis by checking the normality of the data using the Shapiro-Wilk test, and also testing hypotheses using the t-test. The results obtained are proven by a significant pretest value of 0.083 and posttest of 0.088, which shows that sig is >0.05 so ????0 is acceptable. The results of the normality test in the experimental class were also obtained which can be seen in table 5. The pretest obtained a significant value of 0.107 and the posttest of 0.161, which shows that the sig is >0.05 so that ????0is acceptable. Apart from that, the results of hypothesis testing show that the significance value in the control class is a sig(2-tailed) value of 0.005, while in the experimental class the sig(2-tailed) value is 0.006, so it can be concluded that there is a control class and an experimental class that has a sig<0, 05 which means ????1 is accepted and ????0is rejected.